Antigenotoxicity properties of Copaifera multijuga oleoresin and its chemical marker, the diterpene (-)-copalic acid - Alves, Jacqueline Morais; Leandro, Luis Fernando; Senedese, Juliana Marques; Castro, Pamela Tinti de; Pereira, Daiane Eleuterio; Resende, Flavia Aparecida; Campos, Debora Leite [UNESP]; Mangabeira da Silva, Jonas Joaquim; Varanda, Eliana Aparecida [UNESP]; Bastos, Jairo Kenupp; Ambrosio, Sergio Ricardo; Tavares, Denise Crispim (Taylor & Francis Inc, 2018)
In view of the biological activities and growing therapeutic interest in oleoresin obtained from Copaifera multijuga, this study aimed to determine the genotoxic and antigenotoxic potential of this oleoresin (CMO) and its chemical marker, diterpene (-)-copalic acid (CA). The micronucleus (MN) assay in V79 cell cultures and the Ames test were used for in vitro analyses, as well as MN and comet assays in Swiss mice for in vivo analyses. The in vitro genotoxicity/mutagenicity results showed that either CMO (30, 60, or 120 mu g/ml-MN assay; 0.39-3.12 mg/plate-Ames test) or CA (2.42; 4.84, or 9.7 mu g/ml-MN assay; 0.39-3.12 mg/plate-Ames test) did not induce a significant effect on the frequency of MN and number of revertants, demonstrating an absence of genotoxic and mutagenic activities, respectively, in vitro. In contrast, these natural products significantly reduced the frequency of MN induced by methyl methanesulfonate (MMS), and exerted a marked inhibitory effect against indirect-acting mutagens in the Ames test. In the in vivo test system, animals treated with CMO (6.25 mg/kg b.w.) exhibited a significant decrease in rate of MN occurrence compared to those treated only with MMS. An antigenotoxic effect of CA was noted in the MN test (1 and 2 mg/kg b.w.) and the comet assay (0.5 mg/kg b.w.). Data suggest that the chemical marker of the genus Copaifera, CA, may partially be responsible for the observed chemopreventive effect attributed to CMO exposure.
Keywords: Copaifera multijuga Hayne; (-)-copalic acid; genotoxicity; antigenotoxicity; micronucleus test; Ames test; comet assay